2018
DOI: 10.1038/s41386-018-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, genetic and epigenetic contributions to cocaine addiction

Abstract: Decades of research on cocaine has produced volumes of data that have answered many important questions about the nature of this highly addictive drug. Sadly, none of this information has translated into the development of effective therapies for the treatment of cocaine addiction. This review endeavors to assess the current state of cocaine research in an attempt to identify novel pathways for therapeutic development. For example, risk of cocaine addiction is highly heritable but genome-wide analyses comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 154 publications
2
52
0
2
Order By: Relevance
“…Genetic factors account for approximately 50% of the inter-individual differences in cocaine dependence (Ho et al, 2010). Despite the high heritability of cocaine dependence, very few genome-wide studies have investigated cocaine dependence (Pierce et al, 2018). A recent study identified a single nucleotide polymorphism in FAM53B significantly associated with cocaine dependence (Gelernter et al, 2014).…”
Section: Alcoholmentioning
confidence: 99%
“…Genetic factors account for approximately 50% of the inter-individual differences in cocaine dependence (Ho et al, 2010). Despite the high heritability of cocaine dependence, very few genome-wide studies have investigated cocaine dependence (Pierce et al, 2018). A recent study identified a single nucleotide polymorphism in FAM53B significantly associated with cocaine dependence (Gelernter et al, 2014).…”
Section: Alcoholmentioning
confidence: 99%
“…Posttranslational modifications to histones and chromatin remodeling are dynamic epigenetic processes that alter access of transcriptional machinery to promoter regions, thereby regulating patterns of gene expression (Strahl and Allis, 2000;Berger, 2007). A growing body of evidence indicates that chromatin remodeling, including stable enzymatic modifications of DNA and histone proteins, is associated with persistent changes in gene expression that may underlie drug addiction (Renthal and Nestler, 2008;Maze and Nestler, 2011;Pierce et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The enduring impact of these drugs, even after long periods of abstinence, has suggested persistent molecular events caused by transcriptional, epigenetic and translational effects [1] within addiction-related brain regions [2], such as the nucleus accumbens (NAc), prefrontal cortex (PFC), and hippocampus. Notably, a growing body of evidence has shown the important role of epigenetic regulation in the effects of psychostimulants [3] ( e.g., cocaine [4,5]) and found modifications of histones present in chromatin [6,7], DNA methylation [8,9], and DNA hydroxymethylation involved in the development of addiction. With respect to METH, however, only a few studies have investigated the epigenetic effects of these drugs, mainly focusing on the NAc and striatum [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%